Organic geochemical characterization of Cretaceous - Eocene shale and mudstone in Belaga Formation - Ibrahim, W.E. (Institute of Physics, 2022)
Sarawak Basin has been very prominence for increasing hydrocarbon potential in their formations and its nature as a source rock. Previous studies highlighting more on the evaluation of geochemical characteristics of Paleogene-Neogene coals as the source rock without taking into consideration shales and mudstones in the area. The targets of the study are to evaluate the potentiality of the hydrocarbons, the type of organic matter and thermal maturity of shales and mudstones of Belaga Formation, mainly by using data of Rock-Eval pyrolysis and vitrinite reflectance data. Twenty-one outcrops with twenty-nine samples from Belaga Formation shales and mudstones in the Central Sarawak Basin were analyzed by means of geochemical techniques. The shales and mudstones samples of the Belga Formation has low value of S2 ranging between 0.02-0.66 mg HC/g rock with an average 0.09 mg HC/g rock, indicating that the formation has poor hydrocarbon generative potential. There is lack of hydrogen-rich in the organic matter content in the Formation samples, that were affect the quality of source rocks to be evaluated as good source rock. Geochemical data (Rock-Eval) Tmax values ranging from 316 and 607Â°C for shales and mudstones formations and indicating various histories of maturation within the Formation. The level of the maturation is various from immature, late mature to post mature. The production index (PI) values of the studied samples in Belaga Formation ranging from 0.12-0.65 mg HC/g rock. Â© Published under licence by IOP Publishing Ltd.